2020
DOI: 10.1038/s41598-020-59096-y
|View full text |Cite
|
Sign up to set email alerts
|

Subjective semantic surprise resulting from divided attention biases evaluations of an idea’s creativity

Abstract: the evaluation of an idea's creativity constitutes an important step in successfully responding to an unexpected problem with a new solution. Yet, distractions compete for cognitive resources with the evaluation process and may change how individuals evaluate ideas. in this paper, we investigate whether attentional demands from these distractions bias creativity evaluations. this question is examined using 1,065 creativity evaluations of 15 alternative uses of everyday objects by 71 study participants. partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 78 publications
(83 reference statements)
1
11
0
Order By: Relevance
“…That is, no significant relationships were found between the measured thought dynamics and the originality and usefulness attributed to the participants' ideas by the expert raters while negative relationships were found for spontaneous and free moving thoughts with the difference between expert-rated and self-reported usefulness and originality in particular. Taken together, these findings confirm previous research suggesting that the spontaneity (e.g., Calic et al, 2020;Kounios & Beeman, 2015;Ross & Vall ee-Tourangeau, 2022) and free moving dynamic of one's thoughts (e.g., de Rooij et al, 2018;Guilford, 1967;Mednick, 1962;Wu & Koutstaal, 2020) positively relate to creativity. Thought context-whether thoughts occur on task or off task, or thinking occurs during on-task or offtask activities-in itself did not enhance creativity.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…That is, no significant relationships were found between the measured thought dynamics and the originality and usefulness attributed to the participants' ideas by the expert raters while negative relationships were found for spontaneous and free moving thoughts with the difference between expert-rated and self-reported usefulness and originality in particular. Taken together, these findings confirm previous research suggesting that the spontaneity (e.g., Calic et al, 2020;Kounios & Beeman, 2015;Ross & Vall ee-Tourangeau, 2022) and free moving dynamic of one's thoughts (e.g., de Rooij et al, 2018;Guilford, 1967;Mednick, 1962;Wu & Koutstaal, 2020) positively relate to creativity. Thought context-whether thoughts occur on task or off task, or thinking occurs during on-task or offtask activities-in itself did not enhance creativity.…”
Section: Discussionsupporting
confidence: 89%
“…For example, Ding et al's (2021) empirical findings suggest that uses of common objects that are subjectively perceived as more novel are also better remembered in the longer term, likely because they are more salient among other ideas. In addition, Calic et al (2020) suggest that eliciting surprise through distraction influences the subjective valuation of creativity, irrespective of the objective degree of creativity attributed to an idea. This is complemented by studies on insight problem solving and the AHA!…”
mentioning
confidence: 99%
“…Therefore, many studies have reported that cognitive load should be reduced to enhance creative performance. However, some researchers have shown cognitive load and creative performance to be positively correlated (Calic et al, 2020), indicating that cognitive load improves creative thinking (particularly with respect to partial changes), whereas it negatively affects nonlinear creative thinking. Accordingly, we propose the following hypothesis: Moreover, cognitive load affects the operation of working memory and aids in divergent thinking (fluency) and convergent thinking (selection of concepts with greater originality through inductive thinking) during the creative process (Redifer et al, 2019).…”
Section: Creative Performancementioning
confidence: 99%
“…In our review of the literature, leadership, creativity and innovation were analysed in various ways, including self‐assessments, supervisor assessments and peer assessments. However, it is important to note that these evaluations may be influenced by personal and contextual biases (Calic et al., 2020; Kaufman, 2006, 2019; Mueller et al., 2012; Ng & Feldman, 2012; Paulus & Van der Zee, 2004; Podsakoff et al., 2012; Proudfoot et al., 2015). Self‐evaluations of creativity and innovation have been shown to be inflated, while individuals who experience workplace mistreatment often report negative self‐perceptions (Hershcovis & Reich, 2013; Ng & Feldman, 2012).…”
Section: Moving Forwardmentioning
confidence: 99%